THE WAYS OF SYMPATHETIC SYSTEM OVERACTIVITY BLOCKING: RILMENIDINE VERSUS ATENOLOL - Y. R. Kasherininov; E. K. Shavarova; A. A. Shavarov; N. V. Vachrameeva; A. N. Krutikov; E. V. Smirnova; A. O. Коnrady; E. V. Shlyakhto (Столичная издательская компания, 2016)
Aim. To evaluate effects of long-term treatment with rilmenidine compared with atenolol on lipid and glucose metabolism and cardiovascular remodeling in hypertension. Material and methods. 37 patients with hypertension were randomized to rilmenidine 1-2 mg/day or atenolol 50-100 mg/day for 26 weeks. Standard oral glucose tolerance test with a parallel measurement of insulin and glucose levels was performed. The "areas under the curve" (AUC) for insulin and glucose were calculated. Plasma lipids, left ventricular mass index (LVMI) and intima-media thickness (IMT) were measured. Brachial artery diameter during reactive hyperemia was used to test endothelium-dependent vasodilatation (EDVD). Results. Blood pressure reduction was equally achieved in both treatment arms. The fasting glucose level increased in the atenolol group from 4.8±0.6 to 5.2±0.7 mmol/l (p<0.01). The AUC of glucose in rilmenidine group decreased from 860±93 to 737±66 mmol/min/l (p<0.05), and it increased from 937±86 to 989±88 mmol/min/l (p<0.05) in the atenolol group. Rilmenidine showed a positive effect on lipid levels, while in the atenolol group a significant decrease of high density lipoprotein was observed. LVMI decreased with rilmenidine by 9.6% (p<0.05) and by 6,9% (not significantly) with atenolol. IMT significantly decreased in the rilmenidine. EDVD slightly increased on rilmenidine, while on atenolol group it remained unchanged. Conclusion. Our data suggest that in hypertensive patients central inhibition of sympathetic drive can produce favorable effects on glucose and lipid metabolism compared with standard β-blockade with a similar antihypertensive efficacy. Rilmenidine also provides beneficial effects on cardiovascular remodeling and altered endothelial function in hypertension.